Automatic detection of different types of small-bowel lesions on capsule endoscopy images using a newly developed deep convolutional neural network - Otani, Keita; Nakada, Ayako; Kurose, Yusuke; Niikura, Ryota; Yamada, Atsuo; Aoki, Tomonori; Nakanishi, Hiroyoshi; Doyama, Hisashi; Hasatani, Kenkei; Sumiyoshi, Tetsuya; Kitsuregawa, Masaru; Harada, Tatsuya; Koike, Kazuhiko (Endoscopy, 2020)
Background Previous computer-aided detection systems for diagnosing lesions in images from wireless capsule endoscopy (WCE) have been limited to a single type of small-bowel lesion. We developed a new artificial intelligence (AI) system able to diagnose multiple types of lesions, including erosions and ulcers, vascular lesions, and tumors.Methods We trained the deep neural network system RetinaNet on a data set of 167 patients, which consisted of images of 398 erosions and ulcers, 538 vascular lesions, 4590 tumors, and 34 437 normal tissues. We calculated the mean area under the receiver operating characteristic curve (AUC) for each lesion type using five-fold stratified cross-validation.Results The mean age of the patients was 63.6 years; 92 were men. The mean AUCs of the AI system were 0.996 (95 %CI 0.992 – 0.999) for erosions and ulcers, 0.950 (95 %CI 0.923 – 0.978) for vascular lesions, and 0.950 (95 %CI 0.913 – 0.988) for tumors. Conclusion We developed and validated a new computer-aided diagnosis system for multiclass diagnosis of small-bowel lesions in WCE images.